Variations in Dysbindin-1 are associated with cognitive response to antipsychotic drug treatment - Diego Scheggia; Rosa Mastrogiacomo; Maddalena Mereu; Sara Sannino; Richard E. Straub; Marco Armando; Francesca Managò; Simone Guadagna; Fabrizio Piras; Fengyu Zhang; Joel E. Kleinman; Thomas M. Hyde; et al. (Nature Communications, 2018)
Patients with schizophrenia show varied response to antipsychotics. Here, the authors demonstrate in patients under antipsychotics treatment that a haplotype associated with lower dysbindin-1 expression correlated with better executive functions, providing further mechanistic support from mouse models.